PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GROUP TO GROUP TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMAN 14 PADANG TAHUN PELAJARAN 2013/2014 - Wulandari, Sri; Rahmi, Rahmi; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTThe background of  this research  is the students comprehension of mathematical concepts is low and the students that have more ability are less share the low ability students. To solve the problem by implement active learning type Group To Group. The research purpose is to determine whether the students comprehension of mathematical concepts by implementing active learning type of Group To Group is better than students with an comprehension of mathematical concepts by implementing conventional teaching class XI IPS SMAN 14 Padang lesson year 2013/2014. The type of this  research is experimental research, with a random design on the subject. Sampling was done randomly, chosen as the experimental class is a XI IPS4  and as control class is XI IPS1. The instrument used was a test of comprehension of mathematical concepts in the from of essays with a reliability test is = 0,93. Based on the analysis of data samples know to both classes have a normal distribution and homogeneous variance. Hypothesis testing using t-test. From the calculation  > , so hypothesis is accepted then the confidence interval 95%. Based on the hypotesis test results concluded  that the students comprehension of mathematical concepts that implement active learning type of Group To Group better than students comprehension of mathematical concept with conventional learning.